ANALISIS PELAKSANAAN PRAKTIKUM ANATOMI FISIOLOGI TUMBUHAN JURUSAN PENDIDIKAN BIOLOGI SEMESTER GENAP TAHUN AKADEMIK 2016/2017 - Ahmad Ali (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2017)
This research is descriptive research which aims to know the implementation of Physiology Plant Anatomy practicum in the even semester of academic year 2016/2017. The subject of this research is the fourth semester student of Biology Education Department of Faculty of Tarbiyah and Teacher Training UIN Alauddin Makassar which amounts to 70 people. The focus of the research emphasizes on the practicum implementation of Plant Physiology Anatomy covering the time available, preparation of practicum, the process of implementation as well as laboratory facilities and infrastructure. Technique of collecting data with laboratory documentation in the form of inventory list, attendance list practice and lecturer; Questionnaires were given to the practitioners to find out their responses to the practicum of plant physiology natomi; Interviews were also conducted with praktikan as secondary data. Data were analyzed by quantitative descriptive approach. The results showed that the allocation of time for each practical activity was in the category of less good with the percentage of respondents by 59%; Preparation of the practice is in good category with a percentage of 72%. Implementation of practicum with 65% percentage is in medium category; The availability of laboratory advice and prerequisites is in the moderate category with a percentage of 61%.